The research and evaluation of serious games: Toward a comprehensive methodology. (28th May 2013) - Mayer, Igor; Bekebrede, Geertje; Harteveld, Casper; Warmelink, Harald; Zhou, Qiqi; van, Theo; Lo, Julia; Kortmann, Rens; Wenzler, Ivo
Abstract The authors present the methodological background to and underlying research design of an ongoing research project on the scientific evaluation of serious games and/or computer‐based simulation games (SGs) for advanced learning. The main research questions are: (1) what are the requirements and design principles for a comprehensive social scientific methodology for the evaluation of SGs?; (2) to what extent do SGs contribute to advanced learning?; (3) what factors contribute to or determine this learning?; and (4) to what extent and under what conditions can SG‐based learning be transferred to the real world? In the Netherlands between 2005 and 2012, several hundred SG sessions with 12 SGs were evaluated systematically, uniformly and quantitatively to create a dataset, which comprises data on 2488 respondents in higher education or work organizations. The authors present the research model, the quasi‐experimental design and the evaluation instruments. This focus in this paper is on the methodology and dataset, which form a sound foundation for forthcoming publications on the empirical results.